DESIGN AND BUILD A WEB-BASED INVENTORY APPLICATION USING THE WATERFALL METHOD ON CV PERDANA BERKAH SEJAHTERA BANDUNG - Yusuf Bachtiar,; Fuad Nur Hasan, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Web-based inventory applications have become an important role in managing inventory in various companies. The purpose of this research is to design a website-based inventory application that aims to assist companies in managing and monitoring inventory efficiently. This application will utilize website and database technology to provide the features needed by companies in their inventory management. CV Perdana Berkah Sejahtera is a company engaged in general trading in the Bandung area. This company is more likely to be engaged in sales such as Office Stationery, Computers, Laptops, Chemicals, Computer Accessories and others. As for the stock management system, it still uses manual recording through paper media which is carried out by employees, data is easily damaged and lost, and errors often occur in recording inventory. The research method used is the waterfall model software development method, observation, interviews, literature study. The result of this research is the formation of a website-based application that can provide effective and efficient solutions in stock management.